(untitled) (Global Journal of Management and Business Research, 2020)
Fintech is a multi-billion-dollar industry and it has been growing rapidly in India in the last five years and is expected to grow further in the near future. Due to the current situation of pandemic, Fintech companies are leading the way in a world where digital transactions are at an all-time high. According to the National Investment Promotion and Facilitation Agency- "The Indian Fintech market is currently valued at 31 Bn and is expected to grow to 84 Bn by 2025, at a CAGR of 22%.The current state of the Indian FinTech industry is the result of a unique mix of technical enablers, governmental interventions, and economic prospects, as well as certain additional characteristics exclusive to India. Over 67 percent of India’s 2,100+ FinTechs were founded in the last five years. In the quarter of June 2020, 33 new FinTech investment deals worth US647.5 million were closed in India, compared to US284.9 million in China. Overall, the FinTech market in India is already worth US31 billion and is expected to grow to US84 billion by 2025. By 2023, the value of FinTech transactions is expected to increase to US138 billion, up from US66 billion in 2019. In this paper an attempt has been made to explain and analyse the reasons for the growth of Fintech industry, potential challenges and prospects this industry is experiencing in current time period in the Indian context.